The Vacuolar ATPase from Entamoeba histolytica: Molecular cloning of the gene encoding for the B subunit and subcellular localization of the protein - Meléndez-Hernández, Mayra Gisela (BioMed Central, 2008)
BACKGROUND: Entamoeba histolytica is a professional phagocytic cell where the vacuolar ATPase plays a key role. This enzyme is a multisubunit complex that regulates pH in many subcellular compartments, even in those that are not measurably acidic. It participates in a wide variety of cellular processes such as endocytosis, intracellular transport and membrane fusion. The presence of a vacuolar type H(+)-ATPase in E. histolytica trophozoites has been inferred previously from inhibition assays of its activity, the isolation of the Ehvma1 and Ehvma3 genes, and by proteomic analysis of purified phagosomes. RESULTS: We report the isolation and characterization of the Ehvma2 gene, which encodes for the subunit B of the vacuolar ATPase. This polypeptide is a 55.3 kDa highly conserved protein with 34 to 80% identity to orthologous proteins from other species. Particularly, in silico studies showed that EhV-ATPase subunit B displays 78% identity and 90% similarity to its Dictyostelium ortholog. A 462 bp DNA fragment of the Ehvma2 gene was expressed in bacteria and recombinant polypeptide was used to raise mouse polyclonal antibodies. EhV-ATPase subunit B antibodies detected a 55 kDa band in whole cell extracts and in an enriched fraction of DNA-containing organelles named EhkOs. The V-ATPase subunit B was located by immunofluorescence and confocal microscopy in many vesicles, in phagosomes, plasma membrane and in EhkOs. We also identified the genes encoding for the majority of the V-ATPase subunits in the E. histolytica genome, and proposed a putative model for this proton pump. CONCLUSION: We have isolated the Ehvma2 gene which encodes for the V-ATPase subunit B from the E. histolytica clone A. This gene has a 154 bp intron and encodes for a highly conserved polypeptide. Specific antibodies localized EhV-ATPase subunit B in many vesicles, phagosomes, plasma membrane and in EhkOs. Most of the orthologous genes encoding for the EhV-ATPase subunits were found in the E. histolytica genome, indicating the conserved nature of V-ATPase in this parasite.